Exploring Patient Satisfaction with Refraction Examination Services at Optic ARO Gapopin in 2025 - Murni Marlina Simarmata; Febri Maryani; Stepanus Silaban (PROMOTOR, 2026)
This study aims to explore patient satisfaction with refraction examination services at Optic ARO Gapopin in 2025. Using a qualitative descriptive approach, data were collected through in-depth interviews with patients who had undergone refraction examinations. Thematic analysis was employed to identify recurring patterns and perceptions regarding the service. The findings reveal five main themes influencing patient satisfaction: (1) facility comfort, where patients appreciated the modern equipment but noted limited waiting area space; (2) competence and accuracy of examination, as patients trusted the examiners’ skills and found the explanations clear and easy to understand; (3) staff attitude and empathy, with patients highlighting friendliness, patience, and attentiveness; (4) waiting time, which was perceived as relatively long during peak hours; and (5) cost and overall value, where services were considered affordable and proportional to the quality received. In conclusion, patients generally reported being satisfied to highly satisfied with the refraction examination services. The strengths of the service lie in examiner competence and staff empathy, while areas for improvement include waiting time management and waiting area comfort. These findings suggest that enhancing responsiveness and facility convenience could further increase client satisfaction at Optic ARO Gapopin.